Zero Trust Evolution: Advanced Architectures for Resilient Cloud-Native IAM Systems - Arun Ganapathi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the evolution of Zero Trust Architecture (ZTA) and its integration with cloud-native Identity and Access Management (IAM) systems. It presents a comprehensive article analysis of advanced security frameworks in modern distributed environments. The article examines the transformation from traditional perimeter-based security models to sophisticated identity-centric approaches, highlighting the critical role of continuous verification mechanisms and adaptive authentication systems. The article demonstrates how organizations can enhance their security posture while maintaining user privacy and regulatory compliance through surveys of decentralized identity integration, blockchain-based credentials, and self-sovereign identity concepts. The article also delves into system reliability and high availability considerations, exploring fault tolerance strategies, redundancy patterns, and recovery mechanisms essential for maintaining robust security implementations. By analyzing emerging technologies, implementation best practices, and standardization efforts, this research provides valuable insights into the future direction of security architectures. It offers recommendations for organizations navigating the complex landscape of modern cybersecurity challenges.